Public confidence in the auditing profession - Loh, Mei San (2015)
The auditing profession is facing increased number of litigation recently due to corporate failures of their clients whom they audited and had received "clean" reports. How do the users of audited financial information perceive the profession and the work performed by the auditors with all the happenings to the profession? Is the profession able to maintain its credibility and usefulness now? This project serves to ascertain the level of public confidence users have in the auditing profession, the factors contributing to their confidence, and the recommendations deemed necessary to maintain or enhance the profession's image. Research was carried out in two ways: (1) A questionnaire survey was designed to determine public's perception of auditors' competence, integrity, independence, and the exercise of due audit care. It also ascertains whether there is an expectation gap and how in addition to litigation of auditors and high audit staff turnover impact users' confidence in the profession. (2) Literature review based on local and foreign written articles was carried out to supplement and compare findings from the survey. Respondents indicated a more than indifference confidence level of 3.67 (on a scale of 1 to 5) in the profession. Auditors' competence in understanding the clients' businesses received a low rating among all other factors and it is rather highly correlated to public confidence. Auditors' independence and the training by CPA firms reflected fairly good ratings. All these three factors had relatively higher correlations to the confidence level than the other factors. Hence, there must be measures to improve auditors' competence in understanding clients' business; and at a minimum, maintain the current standard of independence and training by CPA firms, so as not to decrease the level of confidence the public has in the profession. The project concluded that users wanted more stringent auditing standards. This would supposedly improve audit quality, thus maintaining or even increase their confidence in the profession. Other favourable recommendations included audit rotation by audit partners or CPA firms; having an independent body to appoint and pay the CPA firms; make audit committees compulsory for all companies; revise the current audit report; and peer review by other CPA firms.